(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Thalassemia syndrome is a heterogeneous group of inherited anemias characterized by abnormalities in tetra hemoglobin synthesis. Objectives: To study the risk factors for delayed growth in patients with thalassemia B who visit the Thalassemia Center at IBN AL Abalady Maternity &Children Hospital in Baghdad. Patients and treatment methods: One hundred thalassemia major patients attending the Thalassemia Center at IBN AL Abalady Maternity &Children Hospital in Baghdad. Were studied during the period from September 1, 2021, to June 30, 2022. Their ages ranged between (5-20) years, including 46 females, and 54 were male. Results. Growth retardation, as a complication of thalassemia, is found in 69% of patients. Patients who required frequent blood transfusions (mean 16.76 blood transfusions/year) developed more growth delay than those who required less frequent blood transfusions (mean 13.67 blood transfusions/year). Conclusions: Growth retardation was found in 69% of thalassemia patients. Most patients were over- or under transfused, and patients who started deferoxamine therapy early and who received it several days a week were less likely to develop growth retardation.